Effect of in situ Sb doping on crystalline and electrical characteristics of n-type Ge1−xSnx epitaxial layer. (29th March 2016) - Jeon, Jihee; Asano, Takanori; Shimura, Yosuke; Takeuchi, Wakana; Kurosawa, Masashi; Sakashita, Mitsuo; Nakatsuka, Osamu; Zaima, Shigeaki
Abstract: We examined the molecular beam epitaxy of Ge1− x Sn x with in situ Sb doping on Ge substrates. The effects of Sb doping on the crystalline and electrical characteristics of Ge1− x Sn x epitaxial layer were investigated in detail. We found that Sb doping with a concentration of 10 20 cm −3 remarkably improves the crystallinity, and surface uniformity of the Ge1− x Sn x epitaxial layer by changing the growth mode by the surfactant effect of Sb atoms. Low-temperature Ge1− x Sn x growth with in situ Sb doping realizes a very high electron concentration of 10 20 cm −3, which is above the thermal equilibrium solid solubility, as a result of suppressing Sb segregation and precipitation.